Serological and molecular typing in platelet alloantibody investigations. (5th November 2019) - Ahlen, Maria Therese
Abstract : Alloimmunization against platelet antigens causes complications in transfusion settings as platelet transfusion refractoriness and post‐transfusion purpura, as well as in pregnancy, causing fetal/neonatal alloimmune thrombocytopenia. Strategies for the laboratory investigations depend on a repertoire of serological and molecular assays and are often dependent on timing and objective. Technical improvements have led to a number of sophisticated methods for alloantigen typing and alloantibody identifications during the last decade; however, some traditional methods are still beneficial. The laboratory investigations should ensure that the causative antibody specificities are identified as soon as possible to support the correct diagnosis and guide the selection of compatible platelets if needed.